To Problem Pertaining to Improvement of Indicators on Fuel Utilization Efficiency in Belarusian Energy System - G. T. Kulakov; A. T. Kulakov; V. V. Kravchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper reveals main shortcomings of an existing target indicator on energy savings for GPO Belenergo. A relative target indicator on energy savings, as well as a cost target indicator on energy savings for ranking regional RUE GPO Belenergo on fuel utilization efficiency are proposed in the paper.